El Excentrico, 1960-02-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
February 20, 1960 [20 de febrero de 1960]. Ano 10, No 12. Cover has a photograph of a actress "Luz Maria Aguelar" with headline "Sonrisas Luminosas - Movie Starlet Luz Maria Aguelar."